Safety and Tolerability of Delayed-Release Dimethyl Fumarate Administered with Interferon Beta or Glatiramer Acetate in Relapsing-Remitting Multiple Sclerosis - Calkwood, Jonathan (Int J MS Care, 2016)
Background: Delayed-release dimethyl fumarate (DMF; also known as gastroresistant DMF) is indicated for relapsing multiple sclerosis (MS). The objective of this study was to explore the safety and tolerability of DMF when administered with interferon beta (IFNβ) or glatiramer acetate (GA). Methods: Patients with relapsing-remitting MS receiving established therapy with the same dose of IFNβ or GA for at least 12 months continued their prescribed therapy for 2 months (monotherapy period) and then received DMF 240 mg three times daily in addition to their prescribed MS therapy for 6 months (add-on therapy period). Safety and magnetic resonance imaging outcomes were monitored monthly. Results: During the add-on therapy period, in the DMF+IFNβ (n = 57) and DMF+GA (n = 47) groups, the overall incidence of adverse events was 95% and 100%, respectively; the most common adverse events were flushing, diarrhea, and abdominal pain. In both groups, mean lymphocyte counts decreased but remained within normal limits, and hepatic transaminase levels increased transiently; no case met Hy's law criteria. There was no overall increased risk of infection. In both groups, gadolinium-enhancing lesion activity and new/enlarging T2 lesions decreased compared with the monotherapy period (exploratory endpoints). Conclusions: The safety profile of DMF taken with IFNβ or GA was acceptable and consistent with the known safety profile of DMF monotherapy.